El Criminal Compliance: la responsabilidad penal de las personas jurídicas y el cumplimiento normativo - Abad-Saldaña, Giovanna (2018)
As a part of the expansion of criminal law and the regulation of crimes of abstract danger for the protection of the legal right “common security”, we are facing a new scenario of criminal law in the legal-business field, which proposes a change in the vision that until a decade ago was held about the criminal responsibility of legal persons and the sanctions for crimes committed in the framework of corporate activities. In this new context, it is important to analyze the two doctrinal positions of corporate criminal law, making an important comparison between the legal axiom “societas deliquere non potest” –society can not commit a crime– versus the modern position of criminal responsibility legal persons derived from the criminal activities of their partners, shareholders or representatives that are committed under the corporate veil and using the social structure. Then, there is the figure of regulatory Compliance in the field of criminal law, or criminal Compliance as it is known in Anglo-Saxon law; This, relatively new, legal tool for Western law and for Peruvian criminal law, establishes a new legal order that regulates the correct business performance, distinguishing the liability of the legal entity against the criminal behavior of its partners or representatives. This mechanism of regulatory compliance will be developed in this article, analyzing its context, importance, implications and its projection to the next decades.